Synthesis and photophysical studies of a multivalent photoreactive RuII-calix[4]arene complex bearing RGD-containing cyclopentapeptides - Kajouj, Sofia; Marcelis, Lionel; Mattiuzzi, Alice; Grassin, Adrien; Dufour, Damien; Van Antwerpen, Pierre; Boturyn, Didier; Defrancq, Eric; Surin, Mathieu; De Winter, Julien; Gerbaux, Pascal; Jabin, Ivan; et al. (Beilstein Journal of Organic Chemistry, 2018)
Photoactive ruthenium-based complexes are actively studied for their biological applications as potential theragnostic agents against cancer. One major issue of these inorganic complexes is to penetrate inside cells in order to fulfil their function, either sensing the internal cell environment or exert a photocytotoxic activity. The use of lipophilic ligands allows the corresponding ruthenium complexes to passively diffuse inside cells but limits their structural and photophysical properties. Moreover, this strategy does not provide any cell selectivity. This limitation is also faced by complexes anchored on cell-penetrating peptides. In order to provide a selective cell targeting, we developed a multivalent system composed of a photoreactive ruthenium(II) complex tethered to a calix[4]arene platform bearing multiple RGD-containing cyclopentapeptides. Extensive photophysical and photochemical characterizations of this Ru(II)–calixarene conjugate as well as the study of its photoreactivity in the presence of guanosine monophosphate have been achieved. The results show that the ruthenium complex should be able to perform efficiently its photoinduced cytotoxic activity, once incorporated into targeted cancer cells thanks to the multivalent platform.
Keywords: anticancer drug; calixarene; cell targeting; RGD peptide; ruthenium complex